2016
DOI: 10.1016/j.clinph.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The significance of ultrasonographic carpal tunnel outlet measurements in the diagnosis of carpal tunnel syndrome

Abstract: ). The sponsor had no direct involvement in the collection, analysis and interpretation of data and in the preparation of the manuscript. 2 HIGHLIGHTS Median nerve enlargement in CTS is significantly greater at the tunnel outlet than at the inlet  It is postulated that pressure progressively increases from proximal to distal within the tunnel  The addition of outlet measurements increases diagnostic sensitivity and accuracy of CTS 3 ABSTRACT Objective: A retrospective study to investigate the utility of ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Interestingly, the outlet cross‐sectional area has also shown good diagnostic characteristics as a single parameter, which was recently reported in several studies . Also, we observed that almost half of all symptomatic wrists (64 of 135) had an outlet cross‐sectional area that was at least slightly larger than the inlet cross‐sectional area (and equal to or larger than its cutoff value), whereas 15% of them (7.4% of all symptomatic wrists) had an inlet cross‐sectional that was smaller than or at the cutoff value (10 mm 2 ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Interestingly, the outlet cross‐sectional area has also shown good diagnostic characteristics as a single parameter, which was recently reported in several studies . Also, we observed that almost half of all symptomatic wrists (64 of 135) had an outlet cross‐sectional area that was at least slightly larger than the inlet cross‐sectional area (and equal to or larger than its cutoff value), whereas 15% of them (7.4% of all symptomatic wrists) had an inlet cross‐sectional that was smaller than or at the cutoff value (10 mm 2 ).…”
Section: Discussionsupporting
confidence: 82%
“…Also, we observed that almost half of all symptomatic wrists (64 of 135) had an outlet cross‐sectional area that was at least slightly larger than the inlet cross‐sectional area (and equal to or larger than its cutoff value), whereas 15% of them (7.4% of all symptomatic wrists) had an inlet cross‐sectional that was smaller than or at the cutoff value (10 mm 2 ). Few studies have previously reported similar findings …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Since the first description by Buchberger et al, 5,6 a number of sonographic abnormalities have been reported in individuals with clinical CTS, including: increase in median nerve cross-sectional area (CSA) at the level of the pisiform bone (carpal tunnel inlet) and hamate; increase in nerve CSA at the level of the pisiform bone compared with the area at the distal radius (swelling ratio) or forearm (wrist-to-forearm ratio); increase in the flattening ratio at the hook of the hamate; palmar bowing of the flexor retinaculum; isolated enlargement of the median nerve in the distal carpal tunnel; and, more recently, changes in nerve echogenicity and vascularity. [7][8][9][10][11] The most consistent finding in the literature, however, is an increase in the median nerve CSA at the level of the pisiform bone. 3,7 There is supporting level A evidence that median nerve CSA at the wrist is reliable and can be offered "as an accurate diagnostic test for CTS."…”
mentioning
confidence: 74%
“…Nerve ultrasound is increasingly being adopted into clinical neurophysiology practice for evaluation of CTS. Since the first description by Buchberger et al ., a number of sonographic abnormalities have been reported in individuals with clinical CTS, including: increase in median nerve cross‐sectional area (CSA) at the level of the pisiform bone (carpal tunnel inlet) and hamate; increase in nerve CSA at the level of the pisiform bone compared with the area at the distal radius (swelling ratio) or forearm (wrist‐to‐forearm ratio); increase in the flattening ratio at the hook of the hamate; palmar bowing of the flexor retinaculum; isolated enlargement of the median nerve in the distal carpal tunnel; and, more recently, changes in nerve echogenicity and vascularity …”
mentioning
confidence: 99%